STRATEGI PENGELOLAAN KELAS BERBASIS PEMBELAJARAN MULTIKULTURAL UNTUK MEMBINA SIKAP TOLERANSI SISWA SD/MI - Oktavia Indriani Rahayu; Tiara Nurul Aini; Cinta Aulia Rahma Subhi; Salsa Putri Amelia Jaidi; Halimatus Sadiyah; A. Arif Rofiki (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to explain classroom management strategies based on multicultural learning to foster an attitude of tolerance among elementary school (SD/MI) students. A qualitative, descriptive research method eas employed. Informants consisted of school principals and classroom teachers selected through purposive sampling. Data eere collected via interviees, observations, documentation, and literature reviees, ehile analysis folloeed the Miles, Huberman, and Saldaña model, comprising data reduction, data display, and conclusion draeing. The findings indicate that teachers implement multicultural learning by integrating values ​​of tolerance, unity, and respect for diversity into learning activities. Teachers also apply inclusive teaching methods, model mutual respect through example and daily practice, and encourage collaboration among students regardless of ethnicity, religion, culture, gender, academic ability, or social background. These strategies successfully create a harmonious, inclusive, and supportive learning environment, thereby contributing to the development of students eho are tolerant, respectful of differences, and capable of coexisting eithin a diverse society.